Compression Degree of Trigeminal Nerve and Type of Conflicting Vessels Determine Short- and Long-Term Complete Pain Relief in Adult Patients with Primary Trigeminal Neuralgia After Microvascular Decompression: A Three-Year Retrospective Study of 200 Adult Patients with Primary Trigeminal Neuralgia - Zhao ZF; Liu BB; Zhang JN; Shi N; Zhang P; Yang GZ; Cao YF; Tian LH; Qiu CC; Gao Y (Journal of Pain Research, 2023)
Zhe-Feng Zhao,1,* Bing-Bing Liu,1,* Jian-Nan Zhang,2,* Ni Shi,3,* Ping Zhang,1,* Gang-Zhi Yang,4 Yu-Fu Cao,4 Long-He Tian,4 Cheng-Cai Qiu,5 Yang Gao6,7 1Department of Neurosurgery, The Second Affiliated Hospital of Harbin Medical University, Harbin, Heilongjiang, People’s Republic of China; 2Department of Critical Care Medicine, The First Affiliated Hospital of Harbin Medical University, Harbin, Heilongjiang, People’s Republic of China; 3Department of Critical Care Medicine, The Second Affiliated Hospital of Harbin Medical University, Harbin, Heilongjiang, People’s Republic of China; 4Department of Neurosurgery, People’s Hospital of Hegang City, Hegang, Heilongjiang, People’s Republic of China; 5Department of Neurosurgery, Traditional Chinese Medicine Hospital of Jixi City, Jixi, Heilongjiang, People’s Republic of China; 6Department of Critical Care Medicine, The Sixth Affiliated Hospital of Harbin Medical University, Harbin, Heilongjiang, People’s Republic of China; 7Institute of Critical Care Medicine, The Sino Russian Medical Research Center of Harbin Medical University, Harbin, Heilongjiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhe-Feng Zhao, Department of Neurosurgery, The Second Affiliated Hospital of Harbin Medical University, Harbin, People’s Republic of China, Email know810512@163.com Yang Gao, Department of Critical Care Medicine, The Sixth Affiliated Hospital of Harbin Medical University, Harbin, People’s Republic of China, Email gaoyang0312@126.comObjective: In this study, we aimed to explore the demographic and clinical factors that could determine short- and long-term complete pain relief (CPR) in adult patients with primary trigeminal neuralgia (PTN) after microvascular decompression (MVD) to guide clinical practice.Methods: This single-center retrospective study included adult patients with PTN who underwent MVD as their initial neurosurgical procedure in the Department of Neurosurgery at the Second Affiliated Hospital of Harbin Medical University from January 2017 to December 2019 and completed a 3-year post-surgery follow-up. Demographic and clinical information was obtained from medical records. Pain relief of adult patients with PTN at various time points after sufficient decompression of trigeminal nerve (TN) during MVD was determined and classified by the patient’s subjective response and medications use. Pain relief of local patients was evaluated by outpatient follow-up at various time points, whereas that of local cases who could not return to outpatient or non-local cases was assessed through telephone or WeChat.Results: In univariate analysis, compression degree of TN and type of conflicting vessels constantly showed significant differences between the two groups at 3 months, 6 months, 1 year, 2 years, and 3 years after MVD. Compression degree of TN and type of conflicting vessels at various time points after MVD were always the related factors to CPR in logistic regression analysis, with the former having the greatest impact. The areas under the receiver operating characteristic (ROC) curve of CPR at various time points after MVD were 0.937, 0.874, 0.879, 0.864, and 0.869, respectively.Conclusion: In summary, compression degree of TN and type of conflicting vessels can determine short- and long-term CPR in adult patients with PTN after MVD.Keywords: compression degree of trigeminal nerve, type of conflicting vessels, microvascular decompression, sufficient decompression of trigeminal nerve, complete pain relief, primary trigeminal neuralgia